Quality of life of patients with traumatic brachial plexus injuries - Estrella, Emmanuel P.
Introduction: Traumatic brachial plexus injuries usually occur in younger individuals and usually result in lifelong disability and pain. Most outcome studies only rely on nerve impairment and motor weakness or disability. The objective of this paper was to determine the quality of life of patients with traumatic brachial plexus injuries. The specific objectives were: to determine the validity of the culturally-translated DASH outcome questionnaire (FILIPINO DASH), to determine the mean FILIPINO DASH score to determine the factors associated with the FILIPINO DASH score for patients with traumatic brachial plexus injuiries. Study Design: This was a cross-sectional study that evaluated adult patients with traumatic brachial plexus injuries with at least six months from the time of their injury. Study Setting: The study setting was at the University of the Philippines, Manila, Microsurgery Unit of the Department of Orthopedics, Philippine General Hospital. Patient Population: Included were patients with traumatic brachial injuries with atleast six months from injury to the time of evaluation, six months from the time of surgery and who are able to answer the self-reported questionnaire. excluded were patients with obstetric brachial plexus injuries, who are unable to understand Filipino and who are mentally incapable of answering the self reported questionnaire. The study was conducted in two phases. The first phase was the translation DASH into Filipino and validation of the FILIPINO DASH score. The cultural translation of the DASH score to the Filipino DASH was approved by the propriety owners (DASH Outcome Measure: Institute for Work and Health, Ontario, Canada). After the translation process, the Filipino DASH was tested for validity and reliability. Internal consistency was tested using the Cronbach's alpha with an alpha of ->0.70 as acceptable. Test rest reliability was conducted on two separate occasions at 7-14 days apart. An interclass correlation coefficient (ICC) of ->0.75 was regarded as very good. The respondents did face validity where the questions were assessed as understandable and relevant to their inquiry. Finally, construct validity using the Pearson's correlation coefficient was done by correlating the FILIPINO DASH scores with the tagalog version of the SF-36 scores, where a correlation coefficient of -> -0.40 -0.70 was deemed as having a moderate correlation and a correlation coefficient of ->0.70 was judged as having a high correlation. All statistical significance was conducted if p-<0.05. The validity analysis on the FILIPINO DASH was used in testing our first hypothesis.